2017
DOI: 10.1039/c6nr07313a
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation-enabled rapid and tunable evolution of high-χN micelles as templates for ordered mesoporous oxides

Abstract: The kinetic-entrapment of block copolymer micelles enables size-persistence, however tuning micelle sizes under such conditions remains challenging. Agitation-induced chain exchange via vortexing is limited by the production of solution-air interfaces. Here, we use ultrasonic cavitation for rapid interface production that accelerates micelle growth by an order of magnitude over vortexing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
0
22
1
1
Order By: Relevance
“…Persistent micelle templates (PMTs) recently emerged as a unique approach to realize isomorphic sample series (constant morphology symmetry) with independent control of each feature size, namely the wall‐thickness and pore size. PMT has advanced to span a wide range of dimensions from mesoporous to macroporous materials . PMT is based on kinetic control where micelle exchange mechanisms are suppressed to preserve a constant micelle diameter (constant template).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent micelle templates (PMTs) recently emerged as a unique approach to realize isomorphic sample series (constant morphology symmetry) with independent control of each feature size, namely the wall‐thickness and pore size. PMT has advanced to span a wide range of dimensions from mesoporous to macroporous materials . PMT is based on kinetic control where micelle exchange mechanisms are suppressed to preserve a constant micelle diameter (constant template).…”
Section: Introductionmentioning
confidence: 99%
“…Each film was spin coated for 30 s at 1000, 1500, 2000, and 2150 rpm under 15% relative humidity for each M:T condition of 1.2, 1.8, 2.4, and 3.0, respectively, as described in detail elsewhere. [ 61,63,94 ] Immediately after the end of spin coating, each sample was removed from the humidity‐controlled chamber and placed on a 110 °C hot plate overnight to crosslink the oxide, termed as “aging.” The room humidity during aging was not found to have an effect. Aging conditions were optimized to prevent initial dewetting and to assure sufficient oxide connectivity to survive calcination.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that ultrasound can accelerate micelle growth by an order of magnitude with respect to agitation by vortex [44]. Cavitation effect enhance the production of bubbles, which increases the interfaces air/water.…”
Section: Effect Of Ultrasound On Electrolysismentioning
confidence: 99%